Jet-radius dependence of inclusive-jet cross sections in deep inelastic scattering at HERA - Chekanov, S; Derrick, M; Magill, S; Miglioranzi, S; Musgrave, B; Nicholass, D; Repond, J; Yoshida, R; Mattingly, M; Jechow, M; Pavel, N; Yagües Molina, A; et al. (2007)
Differential inclusive-jet cross sections have been measured for different jet radii in neutral current deep inelastic ep scattering for boson virtualities Q2 > 125   GeV2 with the ZEUS detector at HERA using an integrated luminosity of 81.7 pb-1. Jets were identified in the Breit frame using the kT cluster algorithm in the longitudinally inclusive mode for different values of the jet radius R. Differential cross sections are presented as functions of Q2 and the jet transverse energy, ET, Bjet. The dependence on R of the inclusive-jet cross section has been measured for Q2 > 125 and 500   GeV2 and found to be linear with R in the range studied. Next-to-leading-order QCD calculations give a good description of the measurements for 0.5 ≤ R ≤ 1. A value of αs (MZ) has been extracted from the measurements of the inclusive-jet cross section d σ / d Q2 with R = 1 for Q2 > 500   GeV2: αs (MZ) = 0.1207 ± 0.0014 (stat .)-0.0033+0.0035 (exp .)-0.0023+0.0022 (th .). The variation of αs with ET, Bjet is in a good agreement with the running of αs as predicted by QCD. © 2007 Elsevier B.V. All rights reserved.